2017
DOI: 10.1080/02640414.2017.1307440
|View full text |Cite
|
Sign up to set email alerts
|

Swimming and peak bone mineral density: A systematic review and meta-analysis

Abstract: This meta-analysis aims to determine the effects of regular swimming on bone mineral density (BMD) in young adults (18-30 years). A systematic search was performed in Pubmed, SPORTDiscus and the Cochrane Library from the earliest possible year to March 2016. Swimmers were compared to non-athletic controls (CG) and to high-impact athletes (HIGH). Effect sizes with the Hedges g in random effects models were developed. Fourteen studies met the inclusion criteria and were included in the meta-analyses. Swimmers pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 63 publications
3
30
0
Order By: Relevance
“…The present findings are of critical importance for swimming coaches, kinesiologists, and physicians, as they suggest that whole body vibration, with the performed protocol, is ineffective for improving bone structure and strength during adolescence. Taking into account that jumping interventions are affordable and have demonstrated positive effects on bone mass in children and adolescents, we would encourage trainers to perform jump interventions in order to improve bone mass of adolescent swimmers, who might be at risk of not reaching their peak bone mineral density [32].…”
Section: Discussionmentioning
confidence: 99%
“…The present findings are of critical importance for swimming coaches, kinesiologists, and physicians, as they suggest that whole body vibration, with the performed protocol, is ineffective for improving bone structure and strength during adolescence. Taking into account that jumping interventions are affordable and have demonstrated positive effects on bone mass in children and adolescents, we would encourage trainers to perform jump interventions in order to improve bone mass of adolescent swimmers, who might be at risk of not reaching their peak bone mineral density [32].…”
Section: Discussionmentioning
confidence: 99%
“…Results of the regional and total BMD of athletes of both sexes. important to emphasize that most of the studies indicated showed that swimming has negative or neutral impacts 5,15,25 on BMD.…”
Section: Discussionmentioning
confidence: 98%
“…Along these lines, Bergman et al 3 note that exercises such as swimming, while having fewer osteogenic effects, can reduce the risk of fractures indirectly by maintaining muscle mass and strength. In a recent meta-analysis, Gomez-Bruton et al 15 observed that young swimmers, when compared to their peers undertaking more osteogenic sports, in other words, sports that involve moderate or high loads and impacts (e.g., basketball, soccer and running, among others), have lower BMD values. However, when compared with non-athlete controls, swimmers have similar BMD levels in almost all bone areas.…”
Section: Introductionmentioning
confidence: 99%
“…Serum concentrations of 25-hydroxycholecalciferol would give us a better insight into vitamin D status, however considering our latitude (above 35th parallel north), long hours spent indoors due to training and the low dietary intake of vitamin D in female swimmers, we can suspect that this group is at risk of vitamin D deficiency. Due to the high physical load we are concerned that the current nutrition strategies of some competitive female swimmers together with calcium deficiency and low EA may have a negative impact on bone health, which is further exacerbated by the physical activity in water which lowers the workload against gravity (Gomez-Bruton et al, 2017). Regular monitoring of vitamin D status is necessary in athletes at increased risk of deficiency and suitable supplementation should be advised in case of discovered inadequacy (Desbrow et al, 2014).…”
Section: Discussionmentioning
confidence: 99%